Multiplicity of positive solutions for a third-order boundary value problem with nonlocal conditions of integral type - Sergey Smirnov (Miskolc Mathematical Notes)
We prove the existence of multiple positive solutions for a nonlinear third-order nonlocal boundary value problem by applying Krasnosel’skii’s fixed point theorem. To illustrate the applicability of the obtained results, we consider an example.